Pengaruh Pendekatan Lingkungan Alam Sekitar Terhadap Kemampuan Literasi Sains pada Mata Pelajaran IPA - Ningtyas, Rindiya; Sartika, Septi Budi (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2024)
The low level of scientific literacy among elementary school students remains a challenge in science learning, particularly in applying models that are relevant to real-life contexts. This study aims to describe the effect of the environmental approach on students’ scientific literacy skills and to analyze the level of influence produced. The research employed a quantitative method with a Pre-Experimental design using the One Group Pretest-Posttest model. The subjects were all 30 fourth-grade students of SDN Panderejo. Data were collected through an essay test consisting of 12 items validated by two experts. Data analysis was carried out using the N-gain test to determine the improvement in scientific literacy and the Eta Square test to measure the effect size. The findings indicate that the environmental approach improved students’ scientific literacy with an N-gain score of 0.3 categorized as moderate and an effect size of 0.4 also categorized as moderate. It can be concluded that the environmental approach has a positive impact on enhancing elementary school students’ scientific literacy in science learning with a moderate effect level. Further studies are recommended to apply experimental designs involving two or more classes to obtain more comprehensive analyses.